Loss-of-function mutation in GATA4 causes anomalies of human testicular development - Lourenço, Diana; Brauner, Raja; Rybczyńska, Magda; Nihoul-Fékété, Claire; McElreavey, Ken; Bashamboo, Anu (Proceedings of the National Academy of Sciences - PNAS, 2011)
Approximately 1 of every 250 newborns has some abnormality of genital and/or gonadal development. However, a specific molecular cause is identified in only 20% of these cases of disorder of sex development (DSD). We identified a family of French origin presenting with 46,XY DSD and congenital heart disease. Sequencing of the ORF of GATA4 identified a heterozygous missense mutation (p.Gly221Arg) in the conserved N-terminal zinc finger of GATA4. This mutation was not observed in 450 ancestry-matched control individuals. The mutation compromised the ability of the protein to bind to and transactivate the anti-Müllerian hormone (AMH) promoter. The mutation does not interfere with the direct protein-protein interaction, but it disrupts synergistic activation of the AMH promoter by GATA4 and NR5A1. The p.Gly221Arg mutant protein also failed to bind to a known protein partner FOG2 that is essential for gonad formation. Our data demonstrate the key role of GATA4 in human testicular development.